The Effect of 12 Weeks of Different Exercise Training Modalities or Nutritional Guidance on Cardiometabolic Risk Factors, Vascular Parameters, and Physical Fitness in Overweight Adults: Cardiometabolic High-Intensity Interval Training-Resistance Training Randomized Controlled Study - Garcia-Hermoso, A (NSCA National Strength and Conditioning Association, 2020)
Evidence suggests that exercise training improves cardiometabolic risk factors. The aim of this study was to investigate whether 12 weeks of high-intensity interval training (HIIT), resistance training (RT), concurrent training (CT = HIIT + RT), or nutritional guidance (NG) induced improvements in cardiometabolic risk factors, vascular parameters, and physical fitness in overweight adults, and to compare the responses between the 4 intervention groups. This is a twelve-weeks factorial randomized design examining the effects of different exercise regimes and/or NG on anthropometric and body composition (fat and lean mass at whole body, trunk fat, fat mass index, appendicular muscle mass, and waist circumference); cardiometabolic risk factors and vascular parameters (blood lipids, fasting glucose, blood pressure, flow-mediated dilation [FMD%], aortic pulse wave velocity (PWV), and augmentation index); and physical fitness (cardiorespiratory fitness and handgrip strength). Adjusted mixed linear models revealed a significant improvement in cardiorespiratory fitness (mL·kg-1·min-1): HIIT +8.3, RT +4.1, and CT +6.3 (all p < 0.001). The improvement difference between the groups was statistically significant between the HIIT and NG group (p = 0.014), (time × group interaction F(23.564); p < 0.001; η2partial = 0.365). In addition, the RT and CT groups have a significant positive impact on PWV (m·s-1) (d = 0.391 and 0.229 respectively; p < 0.001, (time × group interaction F(5.457); p = 0.003; η2partial = 0.280). Hereafter, the RT group has a significant positive impact on the FMD (%) in comparison to HIIT, CT, or NG group (time × group interaction F(2.942); p = 0.044; η2partial = 0.174). The main findings of this study are that 12 weeks of HIIT leads to significant improvements in cardiorespiratory fitness, whereas RT resulted in improvements in the vascular profile, supporting the positive effect of both training programs for cardiometabolic risk factors in sedentary and overweight adults. © 2020 NSCA National Strength and Conditioning Association. All rights reserved.